Procedural Tree Modeling with Guiding Vectors. (15th October 2015) - Xu, Ling; Mould, David
Abstract: We propose guiding vectors to augment graph‐based tree synthesis, in which trees are collections of least‐cost paths in a graph. Each node has an associated guiding vector; edges parallel to the guiding vector are cheap, but edges are more expensive when their orientation differs from the guiding vector. We further propose an incremental method for assigning guiding vectors over the graph, in which a node's guiding vector is an incremental rotation of that of its parent. We present a complete procedural system for tree modeling; our use of guiding vectors enables the graph‐based method to produce high‐quality tree models resembling a variety of real‐world tree species.